Impact of Heat Resources on Rice Productivity in the Sarpinsky Lowland - Dedova, E B; Konieva, G N; Borodychev, V V; Shabanov, R M; Dedov, A A; Ivanova, V I; Mandzhieva, T N (KnE Life Sciences, 2019)
The possibility of rice cultivation in the northern areas of rice sowing is determined by the sum of effective air temperatures (Σt ≥ 15 ∘C) over the growing season and its distribution over the vegetation phases of the plants. A long-term statistical and correlation analysis of rice productivity depending on the thermal resources of the Sarpinsky lowland at the Maliye Derbeta meteorological station for the period from 1964 to 2018 (correlation coefficient r = 0.68) is given. It is established that the sum of effective air temperatures varies from 3140.2 to 3999.7 ∘C, while the average annual value is 2820 ∘C. The highest yield (more than 5 t/ha) of rice grains is formed in years with the sum of effective temperatures over 3000 ∘C. The fluctuations of air temperature and their influence on the production process, and the yield of rice grains are analyzed, the results of which can be used as source data in modeling climate change scenarios and predicting rice grain production. The optimal amounts of effective air temperatures for the period April-September, ensuring the realization of the potential productivity of rice in the Sarpinsky lowland conditions, are determined.